The Influence of Green Supply Chain Management on Business Sustainability Through Green Innovation as a Mediating Variable on Natural Color Batik SMEs in Bantul Regency - Cahyaningrum, Erinna Indah; Kusmantini, Titik; Nilmawati, Nilmawati (Westscience Press, 2024)
This study shows how business sustainability is influenced by Green Supply Chain Management (GSCM) and uses the mediating role of Green Innovation (GI) to explain the relationship. The quantitative descriptive method was used in this study. With a sample size of 50 Natural Batik SMEs, the population of this study was all Natural Batik SMEs in Bantul Regency spread across two villages, namely Wukirsari and Trimulyo. The data analysis method used in this study was SmartPLS 3. The results of the study indicate that: 1) GSCM has a positive effect on Business Sustainability; 2) GSCM has a positive effect on Business Sustainability; 3) GI mediates the effect of GSCM on Business Sustainability of Natural Batik UKM in Bantul Regency.